Dissection et maïeutique du corps dansant: naissance et mort textuelles de la danse - Lucas Sérol (Danza e Ricerca)
This paper attempts to question the traditional image of the death of dance in writing, since the text can’t fully restore the choreographic spectacle. Our intuition is that dance is never entirely present in writing, either because it is dissected by the author's pen, or because it is still in process and thus is not really there, not really described. Through images of the autopsy and midwifery, we will analyze texts by Victor Hugo, Colette, Ruth Saint Denis, Isadora Duncan and Serge Lifar in order to question the idea that dance scenes in literature would cause disappointment. The goal is to show how the material offered by these texts allows us to feel, imagine, and create a choreographic act through the act of reading, and therefore to convey some life in writings.